Mechanisms of Disease: Host-Pathogen Interactions between Burkholderia Species and Lung Epithelial Cells - David, Jonathan; Bell, Rachel E.; Clark, Graeme C. (Frontiers in Cellular and Infection Microbiology, 2015)
Members of the Burkholderia species can cause a range of severe, often fatal, respiratory diseases. A variety of in vitro models of infection have been developed in an attempt to elucidate the mechanism by which Burkholderia spp. gain entry to and interact with the body. The majority of studies have tended to focus on the interaction of bacteria with phagocytic cells with a paucity of information available with regard to the lung epithelium. However, the lung epithelium is becoming more widely recognised as an important player in innate immunity and the early response to infections. Here we review the complex relationship between Burkholderia species and epithelial cells with an emphasis on the most pathogenic species, B. pseudomallei and B. mallei. The current gaps in knowledge in our understanding are highlighted along with the epithelial host-pathogen interactions that offer potential opportunities for therapeutic intervention.